Monitoring the industrial aerobic fermentation process in real time - Golobič, Iztok (Acta chimica slovenica, 2000)
Based on measurements of either oxygen concentration in exhaust gas or reaction heat flow, the specific growth rate and biomass concentration during the fermentation of the bacitracin in the 80 m3 industrial batch bioreactor were determined in real time. Used one-parametric linear recursive least squares model with time-varying forgetting factor follows well the non-linear and, in certain phases of the production, very dynamic process of fermentation, and enables simulation of disturbances in industrial process. Estimated parameters agree well with the measurements, acquired off-line, and represent useful new information, which enable better monitoring of the industrial process.
Keywords: aerobni procesi; antibiotic; antibiotiki; bacitracin; biomasa; fermentacija; kemijska kinetika; koncentracija mase; meritve parametrov; metode; tok toplotni; zasledovanje procesov